GRIEVING FOR A MOTHER WHO HAS SUFFERED A PERINATAL LOSS - Firrizqy, Nurani Putri; Wahyuni, Eko Sari; Sudjarwo, Eddi (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2025)
Perinatal loss is a profound grieving experience that is often socially unrecognized, potentially leading to significant psychological distress among mothers. This study aimed to explore the grieving experiences of mothers who experienced perinatal loss. A qualitative descriptive exploratory case study design was employed involving two purposively selected participants in the working area of Ciptomulyo Primary Health Center, Malang City. Data were collected through semi-structured in-depth interviews and home-visit observations. Data analysis was conducted using thematic analysis, including coding, categorization, and theme development based on interview and observational data. The findings identified three main themes: causes of grief, stages of grief, and impacts of grief. The first subject experienced perinatal loss compounded by perceived inadequate health care services but had reached the acceptance stage supported by strong social support and adaptive coping strategies. The second subject experienced recurrent perinatal loss and significant social pressure, resulting in a prolonged depressive phase marked by sleep disturbances, social withdrawal, and suicidal ideation. Variations in grief intensity were influenced by loss context, health care experiences, and levels of social support. This study concludes that maternal grief following perinatal loss is highly individualized and requires context-sensitive psychological support. Future research is recommended to involve a larger and more diverse sample, including mothers with longer post-loss durations, to better understand long-term psychological impacts and protective factors in recovery processes.